TRPV1 Is a Potential Tumor Suppressor for Its Negative Association with Tumor Proliferation and Positive Association with Antitumor Immune Responses in Pan-Cancer. (18th October 2022) - Nie, Rongfang; Liu, Qian; Wang, Xiaosheng
Abstract : Background . Although numerous studies have shown that the expression and activation of TRPV1 have an important role in cancer development, a comprehensive exploration of associations between TRPV1 expression and tumor proliferation, microenvironment, and clinical outcomes in pan-cancer remains insufficient. Methods . From The Cancer Genome Atlas (TCGA) program, we downloaded multiomics data of ten cancer cohorts and investigated the correlations between TRPV1 expression and immune signatures' enrichment, stromal content, genomic features, oncogenic signaling, and clinical features in these cancer cohorts and pan-cancer. Results . Elevated expression of TRPV1 correlated with better clinical outcomes in pan-cancer and diverse cancer types. In multiple cancer types, TRPV1 expression correlated negatively with the expression of tumor proliferation marker genes ( MKI67 and RACGAP1 ), proliferation scores, cell cycle scores, stemness scores, epithelial-mesenchymal transition scores, oncogenic pathways' enrichment, tumor immunosuppressive signals, intratumor heterogeneity, homologous recombination deficiency, tumor mutation burden, and stromal content. Moreover, TRPV1 expression was downregulated in late-stage versus early-stage tumors. In breast cancer, bladder cancer, and low-grade glioma, TRPV1 expression was more inferior in invasive than in noninvasive subtypes. Pathway analysis showed that the enrichment of cancer-associated pathways correlated inversely with TRPV1 expression levels. Conclusion . TRPV1 upregulation correlates with decreased tumor proliferation, tumor driver gene expression, genomic instability, and tumor immunosuppressive signals in various cancers. Our results provide new understanding of the role of TRPV1 in both cancer biology and clinical practice.